The Use of Rubik Cube Media to Improve Students' English Vocabulary at Madrasah Aliyah Maarif Roudlotut Tholibin - Kusuma, Huda Putra; Hidayatullah, Rizky; Pratiwi, Wiwied (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The English vocabulary mastery plays a crucial role in students' language proficiency and communication skills. However, many students struggle with memorizing and effectively using new vocabulary. This study investigates the effectiveness of using Rubik’s Cube as a learning medium to enhance students’ English vocabulary at Madrasah Aliyah Ma'arif Roudlotut Tholibin. The research employs a Classroom Action Research (CAR) method, following the Kemmis and Taggart model, consisting of four stages: planning, action, observation, and reflection. The study involves students from class XI, divided into two groups (XA and XB), using a combination of observations, questionnaires, tests, and documentation for data collection. The findings indicate that integrating Rubik’s Cube into vocabulary learning improves students’ retention, motivation, and engagement. The study also highlights the potential of game-based learning in fostering an interactive and enjoyable learning environment. These results provide valuable insights for educators in developing innovative teaching strategies to enhance English vocabulary acquisition.